2012
DOI: 10.1371/journal.pone.0039171
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Global Dispersal of Chickens in Prehistory Using Ancient Mitochondrial DNA Signatures

Abstract: Data from morphology, linguistics, history, and archaeology have all been used to trace the dispersal of chickens from Asian domestication centers to their current global distribution. Each provides a unique perspective which can aid in the reconstruction of prehistory. This study expands on previous investigations by adding a temporal component from ancient DNA and, in some cases, direct dating of bones of individual chickens from a variety of sites in Europe, the Pacific, and the Americas. The results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 77 publications
3
143
1
2
Order By: Relevance
“…The majority of published chicken genetic research undertaken so far has focused primarily on the origins of domestic fowl in Asia and MSEA Liu et al 2006;Kanginakudru et al 2008), and their routes of translocation across Oceania and on to South America (Storey et al 2008(Storey et al , 2010(Storey et al , 2012. Less emphasis has been placed on the timing of their entry and routes of movement across ISEA, due to insufficient data to link specific modern chicken haplogroups to definitive ancient domestication centres and lineages through ISEA and into Oceania ).…”
Section: Chickensmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of published chicken genetic research undertaken so far has focused primarily on the origins of domestic fowl in Asia and MSEA Liu et al 2006;Kanginakudru et al 2008), and their routes of translocation across Oceania and on to South America (Storey et al 2008(Storey et al , 2010(Storey et al , 2012. Less emphasis has been placed on the timing of their entry and routes of movement across ISEA, due to insufficient data to link specific modern chicken haplogroups to definitive ancient domestication centres and lineages through ISEA and into Oceania ).…”
Section: Chickensmentioning
confidence: 99%
“…There does seem to be consensus between many researchers that there were multiple domestication centres for chickens in India (Kanginaduru et al 2008), Thailand , South and southwest China and/or surrounding areas (Liu et al 2006), and potentially all the above . terra australis 45 Storey et al (2012) originally argued that Haplogroup E chickens were the first to arrive in the Pacific, and made connections between Polynesian explorers and pre-European origins of Haplogroup E chickens in South America. More recently, found that the majority of modern and all ancient chickens in the Pacific were Haplogroup D, rather than the proposed E. Furthermore, and importantly, east of the Solomon Islands the only ancient D haplotype chickens recorded are those possessing a specific signature termed the 'Pacific or Polynesian motif ' (Figure 15.2).…”
Section: Chickensmentioning
confidence: 99%
See 1 more Smart Citation
“…Red Junglefowl still commonly exist in their native habitats (Brickle et al., 2008; Brisbin, 1995) and are clearly distinguishable from domestic chickens (Johnsgard, 1999). Although genetic contributions from multiple Junglefowl species may have played a role in the domestication process (Eriksson et al., 2008; Nishibori, Shimogiri, Hayashi, & Yasue, 2005), archeological and genetic evidence (Fumihito et al., 1994, 1996; Gongora et al., 2008; Storey et al., 2012; Thomson et al., 2014) indicate that Red Junglefowl from Southeast Asia was the primary progenitor of all domestic breeds of modern chickens. In a previous study, we identified substantial haplotype variation in the major histocompatibility complex (MHC) B‐locus of wild Red Junglefowl (Fulton et al., 2016; Nguyen‐Phuc, Fulton, & Berres, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The origin and domestication of chickens has been of interest to people since at least Roman times (Storey et al, 2012). Based on archaeological and historical evidence the domestication of the fowl is thought to have occurred in multiple, independent centres.…”
Section: Introductionmentioning
confidence: 99%